Spatio-temporal correlation between burn hotspots, pasture areas and cattle production at the state of Rondônia between the years of 2002 and 2016 - da Cruz, Weliton Teixeira (2022)
The unsustainable model of land use and occupation in the State of Rondônia is a threat to biodiversity balance, to the biological cycles and to the provision of ecosystem services provided by forests. In this sense, this article presents an analysis of correlation between burn hotspots, pasture areas and bovine production for the State of Rondônia. Research products were deployed such as maps to demonstrate spatial relationship, graphs to demonstrate the historical series and charts to demonstrate the correlation between the variables. Due to the non-adherence of data to normality, Spearman's correlation coefficient was used. Softwares ArcGis version 10.1 and Jamovi version 1.6 were used. The correlation between fires and bovine production in the State was significant, positive and with a week/moderate tendency, with evidence values ranging from 0.282 to 0.400; while for correlation between pasture areas and forest fires was significant with a trend ranging from 0.485 to 0.633; between bovine production and pasture areas, there is a strong correlation with a significative positive trend from 0.833 to 0.914. It is possible to verify an increase in the values of the variables throughout the time series, and correlation between them. In this scenario, it is urgent to adopt public policies for territorial planning and strengthening of fiscalization agencies.